The effect of Nannochloropsis oceanica feed inclusion on rabbit muscle proteome - Ribeiro, D.M. (2021)
Nannochloropsis oceanica is a microalga, highly concentrated in protein and EPA (eicosapentaenoic acid). It has a recalcitrant cell wall that decreases nutrient digestibility. The objective of this study is to evaluate the effect of Nannochloropsis oceanica feed inclusion on the muscle proteome of fattening rabbits. Twenty rabbits were housed in individual cages for 5 weeks and were fed a control diet (n = 10) and one with 4.45% inclusion of microalga, replacing whole soybean meal (n = 10). After slaughter, samples of gastrocnemius muscle were taken for label-free proteomic analysis. A total of 1497 proteins were identified, 46 with differential abundance. Control rabbits had high abundance of proteins related to protein metabolism, suggesting higher muscle protein turnover. They also had higher abundance of structural proteins, suggesting a less tender meat by comparison with algae-fed rabbits. These had high abundance of proteins related to amino acid catabolism (Phe, Tyr) and synthesis (Gln). In addition, they had high abundance of proteins related to protein breakdown, overall suggesting that more tender meat may result from algae feeding